Endoplasmic Reticulum Stress Activation in Alport Syndrome Varies Between Genotype and Cell Type - Wang, Cong; Liang, Shenghui; Xing, Shijia; Xu, Ke; Xiao, Huijie; Deng, Haiyue; Wang, Xiaoyuan; Chen, Liangyi; Ding, Jie; Wang, Fang (Frontiers in Genetics, 2020)
Alport syndrome is a hereditary progressive chronic kidney disease caused by mutations in type IV collagen genes COL4A3/4/5. X-linked Alport syndrome (XLAS) is caused by mutations in the COL4A5 gene and is the most common form of Alport syndrome. A strong correlation between the type of COL4A5 mutation and the age developing end-stage renal disease in male patients has been found. Mutation to the α (IV) chain causes retention of the protein to the endoplasmic reticulum lumen, which causes endoplasmic reticulum stress (ERS) and subsequent exertion of deleterious intracellular effects through the activation of ERS. The exact time point that mutant type IV collagen α chain exerts its deleterious effects remains elusive. In this study, we explored the relationship between the COL4A5 genotype and cell type in ERS activation. We obtained skin fibroblasts from Alport syndrome patients with different COL4A5 mutation categories [i.e., a missense mutation (c.4298G > T, p.Gly1433Val) in exon 47, a splicing mutation (c.1949–1G > A) in intron 25 and an insertion (c.573_c.574insG, p. Pro193Alafs*23) in exon 10], and then reprogrammed these fibroblasts into induced pluripotent stem cells (iPSCs). Interestingly, no significant dysregulation of ERS pathway markers was observed for the three COL4A5 mutant iPSCs; however, significant activation of ERS in COL4A5 mutant fibroblasts was observed. In addition, we found that the activation levels of some ERS markers in fibroblasts varied among the three COL4A5 mutation types. Mutant COL4A5 proteins were demonstrated to have different effects on cells at different stages of ontogenesis, providing a theoretical basis for choosing the timing of intervention. The observed differences in activation of ERS by the COL4A5 mutant fibroblasts may contribute to the intracellular molecular mechanisms that describe the correlation between genotype and clinical features in XLAS.